2020
DOI: 10.3390/ijerph17238844
|View full text |Cite
|
Sign up to set email alerts
|

An mHealth Workplace-Based “Sit Less, Move More” Program: Impact on Employees’ Sedentary and Physical Activity Patterns at Work and Away from Work

Abstract: Background: Most workplace interventions that aim to reduce sedentary behaviour have 38 focused on employees’ sedentary patterns at-work but less have focused on understanding the 39 impact beyond working time. The aim of this study was to evaluate the impact of a 13-week m-40 health workplace-based ‘sit less, move more’ intervention (Walk@WorkApp; W@W-App) on 41 physical activity (PA) and sitting in desk-based employees at-work and away from work. Methods: Participants (n = 141) were assigned by hospital to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…Alternatively, electronic-health (e-health) interventions delivered via computer software have typically decreased sitting time by 14 and 55 min at 3 and 10 months, respectively [ 17 ]. Preliminary evidence suggests that a simple e-health intervention via an activity tracker and mobile application can elicit short-term (3-month) reductions in total daily sitting by an average of 42.4 min/workday [ 18 ]. While reductions in total occupational sitting time are smaller compared to multi-component interventions, reductions of more than 30 min per day are potentially clinically meaningful [ 19 ] and cost effective [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, electronic-health (e-health) interventions delivered via computer software have typically decreased sitting time by 14 and 55 min at 3 and 10 months, respectively [ 17 ]. Preliminary evidence suggests that a simple e-health intervention via an activity tracker and mobile application can elicit short-term (3-month) reductions in total daily sitting by an average of 42.4 min/workday [ 18 ]. While reductions in total occupational sitting time are smaller compared to multi-component interventions, reductions of more than 30 min per day are potentially clinically meaningful [ 19 ] and cost effective [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SB has become a habitual process because it is linked to diverse contexts and activities, such as work, and standing at work is perceived as uncomfortable [65][66][67]. Unsurprisingly, therefore, that others only found significant SB reductions on weekends [20,26]. SB might be less of a reasoned behaviour and more determined by environmental, societal, or habitual factors.…”
Section: Discussionmentioning
confidence: 99%
“…Using technology to communicate tailored feedback and advice might be a more cost-efficient way than regular personal coaching [21][22][23]. Yet, purely computertailored SB interventions having shown reductions in workplace SB did not find these effects when combining working and leisure time SB [24][25][26]. Therefore, a personal coach providing tailored but automated feedback might be the optimal mixture of a low-cost yet personal intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, both intervention groups felt their adherence to the e-health smartphone prompts diminished over the 12 weeks despite elements of social support and encouragement, which is of concern since intervention dose is associated with intervention efficacy [ 20 ] and indicates the limited sustainability of an e-health smartphone intervention among this population [ 20 , 43 ]. Over the 12 week intervention, EMA and focus group data indicated that high workload had a negative impact on participant’s ability to engage with the prompts, with participants in both Prompt 30 and Prompt 60 arms commonly and consistently reporting workload as a factor negatively influencing adherence to breaks.…”
Section: Discussionmentioning
confidence: 99%
“…To date, workplace e-health interventions primarily utilize prompts, cues and self-monitoring as behavior change techniques [ 22 ]. Preliminary evidence from a recent systematic review suggests that workplace interventions consisting of a smartphone application and wearable technology can elicit short-term (3 month) reductions in total daily SB of an average of 42.4 min/workday [ 23 ]. Given that a high proportion (80%) of the working-age population in the UK utilize a smartphone device daily, this highlights the potential for e-health technologies to provide a low-cost and widely accessible alternative to address what has been described as the pandemic of sedentary behavior [ 21 , 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%